2015
DOI: 10.1016/j.cell.2015.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Alike but Different: RAF Paralogs and Their Signaling Outputs

Abstract: RAF links RAS, one of the most potent human oncogenes, to its effector ERK and to proliferation. This role is evolutionarily conserved, but while simpler multicellular organisms express one RAF, mammals have three. This Minireview highlights common and divergent features of RAF paralogs, their signaling outputs, and roles in tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 21 publications
5
116
1
Order By: Relevance
“…Analysis of p-ERK and p-MEK in colonospheres and tumours showed that this pathway was not inhibited upon RAF1-KD. The levels of p-ERK and p-MEK were either comparable between the samples or increased upon RAF1-KD, consistent with previous studies (figure 5A, B) 22. Moreover, we used Lincscloud database to compare the profiles of differentially regulated genes in RAF1-KD with the profiles generated after the treatment with various MEK-inhibitors (figure 5C).…”
Section: Resultssupporting
confidence: 86%
“…Analysis of p-ERK and p-MEK in colonospheres and tumours showed that this pathway was not inhibited upon RAF1-KD. The levels of p-ERK and p-MEK were either comparable between the samples or increased upon RAF1-KD, consistent with previous studies (figure 5A, B) 22. Moreover, we used Lincscloud database to compare the profiles of differentially regulated genes in RAF1-KD with the profiles generated after the treatment with various MEK-inhibitors (figure 5C).…”
Section: Resultssupporting
confidence: 86%
“…This raises the questions of how does the cell selects between respective RAS proteins and maintains respective effector activation. There are several review articles illustrating the current state of the art regarding the activation mechanism of various effectors [9,11,12,13,21,71,72,73]. HRAS, KRAS and NRAS exhibit remarkable differences beyond their common interaction interfaces for regulators and effectors [74,75,76], especially at their C-terminal hypervariable region (S3 Fig), which has different features, including protein-protein interaction [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…g ., CRAF, PI3Kα, RALGDS, PLCε and RASSF5, and their activation [1,4,5,6,7,8,9,10]. CRAF, a serine/threonine kinase, activates the MEK-ERK axis and controls gene expression and cell proliferation [11]. PI3Kα generates phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ) and regulates cell growth, cell survival, cytoskeleton reorganization, and metabolism [12].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is intriguing, as MEK is considered to be the only established direct substrate of BRAF kinase, especially in the light of prior observations that suggested the effects of vemurafenib on the transcriptome were exclusively MEK dependent (Joseph et al, 2010). CRAF, a paralog of BRAF, has been shown to regulate various other kinases such as ASK1, MST2, PLK1, and ROKa in a MEKindependent manner (Desideri et al, 2015). However, in contrast to the regulation of HMGCL by BRAF V600E , these activities of CRAF were found to be associated with the scaffolding role of CRAF and were independent of its kinase activity.…”
mentioning
confidence: 95%